The Deconstruction of the Meaning of Qawwām: A Gender Performativity Perspective - Ahmad Yasir Huda Huda; Safrudin Edi Wibowo; Win Usuluddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The interpretation of QS. An-Nisa' verse 34 has long been one of the most debated topics in gender discourse, particularly regarding the concept of qawwām, which is frequently understood as male leadership over women. This verse has often been cited to justify hierarchical perspectives in gender relations, leading to various interpretations from diverse scholarly viewpoints. This study seeks to deconstruct the meaning of qawwām by analyzing classical and contemporary exegeses through the framework of gender performativity. Using a literature analysis method, the study reveals that classical interpretations typically reflect hierarchical gender norms rooted in the perceived physical superiority and financial responsibility of men, consistent with the socio-historical context of their time. From the perspective of gender performativity, such norms are understood as social constructs perpetuated through repetitive interpretations and religious traditions. In contrast, contemporary exegeses propose more egalitarian interpretations, viewing qawwām as a flexible and dynamic functional responsibility, emphasizing mutuality and gender justice. The study demonstrates that the gender performativity framework can dismantle patriarchal biases in traditional interpretations and offer a new understanding relevant to the challenges of modern society. In conclusion, inclusive interpretations of qawwām provide a vital foundation for fostering equitable and just gender relations. The study underscores the importance of sustaining dialogue between interpretive traditions and contemporary social contexts to ensure that Islamic values remain relevant and responsive to modern challenges.